Incorporating online Manga and Manhwa to entice cognitive reading and writing strategies / Natasha Zuhaimi and Amalia Qistina Castaneda Abdullah - Zuhaimi, Natasha; Castaneda Abdullah, Amalia Qistina (Akademi Pengajian Bahasa, 2021)
This study aims to examine the strategy of incorporating Online Manga and Manhwa to entice cognitive reading and writing strategies. To become good readers and writers, students need to be immersed with the story. Exposure to literacy is not solely by reading physical books. The existence of technology has broadened the horizon of reading materials to be more striking to readers with various genres through the internet realm. In recent years, online Manga and Manhwa have garnered an innumerable number of readers internationally in promoting their culture and entertainment as the primary source of attraction. Multimodality and Dual-coding theory have been used interchangeably to incorporate Online Manga and Manhwa in the field of language and literacy. The multi-modals in Manga and Manhwa have crafted a path for learners to be creative, imaginative, and critical thinkers. With the emergence of Multimodality and Dualcoding theory, the author discussed the potentials and problems of incorporating online Manga and Manhwa in language and literacy. As an innovation to entice students' reading and writing strategies, the author has adopted a strategy from past research to be incorporated to implement the technique of using Online Manga and Manhwa.